Enterovirus specific anti-peptide antibodies - Poh, Chit Laa *; Kirk, Kristin; Chua, Hui Na *; Grollo, Lara (Humana Press, 2015)
Enterovirus 71 (EV-71) is the main causative agent of hand, foot, and mouth disease (HFMD) which is generally regarded as a mild childhood disease. In recent years, EV71 has emerged as a signiﬁcant pathogen capable of causing high mortalities and severe neurological complications in large outbreaks in Asia. A formalin-inactivated EV71 whole virus vaccine has completed phase III trial in China but is currently unavailable clinically. The high cost of manufacturing and supply problems may limit practical implementations in developing countries. Synthetic peptides representing the native primary structure of the viral immunogen which is able to elicit neutralizing antibodies can be made readily and is cost effective. However, it is necessary to conjugate short synthetic peptides to carrier proteins to enhance their immunogenicity. This review describes the production of cross-neutralizing anti-peptide antibodies in response to immunization with synthetic peptides selected from in silico analysis, generation of B-cell epitopes of EV71 conjugated to a promiscuous T-cell epitope from Poliovirus, and evaluation of the neutralizing activities of the anti-peptide antibodies. Besides neutralizing EV71 in vitro, the neutralizing antibodies were cross-reactive against several Enteroviruses including CVA16, CVB4, CVB6, and ECHO13.